Languaging myths and realities : journeys of Chinese international students - Zhang-Wu, Qianqian (Multilingual Matters, 2022)
"Drawing on a digital ethnography of Chinese international students' first semester languaging practices, this book examines how they use their multilingual and multi-modal communicative repertories to facilitate languaging across contexts, in order to suggest how universities might better serve the needs of international students"-- Provided by publisher.
Keywords: Chinese students -- United States.; English language -- Study and teaching (Higher) -- Chinese speakers.; Foreign study -- Social aspects -- United States.; Students, Foreign -- United States.; College freshmen -- Services for -- United States.; Intercultural communication.; Études à l'étranger -- Aspect social -- États-Unis.; Anglais (Langue) -- Étude et enseignement (Supérieur) -- Sinophones.; Étudiants de première année -- Services -- États-Unis.; Communication interculturelle.; LANGUAGE ARTS & DISCIPLINES / Linguistics / General; Chinese students; College freshmen -- Services for; English language -- Study and teaching (Higher) -- Chinese speakers; Foreign study -- Social aspects; Intercultural communication; Students, Foreign; United States